Para‐tertiary butyl catechol (PTBC), an industrial antioxidant induces human platelet apoptosis. Issue 3 (21st November 2018) - Vishalakshi, Gopalapura J.; NaveenKumar, Somanathapura K.; Hemshekhar, Mahadevappa; Mahendra, Madegowda; Kemparaju, Kempaiah; Girish, Kesturu S.
Abstract: The catecholic derivative para‐tertiary butyl catechol (PTBC) is a conventional antioxidant and polymerization inhibitor, which exhibits melanocytotoxic effects and contact dermatitis often leading to occupational leucoderma or vitiligo. Although numerous industrial workers will be in constant exposure to PTBC and its chances of getting entry into blood are most expected, its effect on blood components is still undisclosed. As platelets play a prominent role in dermatitis, inflammation, and immunity, in this study we have evaluated the effect of PTBC on human platelets in vitro. Exposure of platelets to PTBC showed increased reactive oxygen species (ROS), intracellular calcium, cardiolipin oxidation, mitochondrial permeability transition pore( MPTP) formation, activation of caspases, phosphatidylserine (PS) externalization and decreased mitochondrial membrane potential. In addition, there was a significant decrease in cellular glutathione level, increased γ‐glutamyltransferase (GGT) activity and cell death. These findings demonstrate that PTBC could induce toxic effects on blood components, which is often ignored field of research. Since dermal exposure of humans to toxic chemicals covers an important issue in various industries, there is a need of such work to understand and update the long‐term toxicities induced by PTBC usage in industrial sectors and public domain.